(untitled) (International Journal of Physiotherapy, 2014)
Background: Functional Electrical Stimulation (FES) can be used as an alternative to ankle foot orthosis (AFO) for foot drop following upper motor neuron lesions. A few patients with stroke might experience dystonia as part of its symptomatology. Dystonia can appear at presentation of the stroke or they may be delayed. Post stroke dystonia can affect either one side of the body (hemidystonia) or can be segmental or focal. Method: A 20 year old male, known case of post stroke right foot dystonia was put on Functional Electrical Stimulation (FES) for walking. The ODFS pace device was used for stimulating his right evertors and dorsiflexors while walking. He was made to practice walking with the help of FES for 30 minutes every day, 6 days a week for 4 weeks. The outcome measures were 10 meter walk test, Berg Balance Score (BBS) and ankle range of motion. Result: Despite using the FES, patient continued to experience the same gait difficulty i.e. twisting of right leg while walking although he reports having gained confidence while walking. Conclusion: FES could be used as a novel symptomatic treatment for the abnormal contractions present during dystonia. There, however, is limited data for the role of FES in treating dystonia. Keywords: Functional Electrical Stimulation, FES, Stroke, Dystonia, Foot Dystonia